(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Biofilms, complex communities of microorganisms encased within a self-produced extracellular matrix, have a profound impact on various industries and human health. Their ability to adhere to surfaces, including alloys, leads to diverse consequences, ranging from corrosion and fouling to infections and medical device complications. Understanding the electrochemical behavior of biofilms on alloys is crucial for developing effective strategies to mitigate their detrimental effects. Biofilm formation on alloys is a multifaceted process influenced by several factors, including the alloy's composition, surface properties, environmental conditions, and the microorganisms involved. Initial attachment of planktonic cells to the alloy surface is followed by proliferation, differentiation, and the formation of a structured biofilm architecture. The extracellular matrix, composed of polysaccharides, proteins, extracellular DNA, and lipids, provides structural integrity and protection to the biofilm community. The electrochemical behavior of biofilms on alloys is characterized by a complex interplay of microbial metabolism, electron transfer processes, and the alloy's electrochemical properties. Microorganisms within the biofilm can engage in various metabolic activities, such as respiration, fermentation, and methanogenesis, which generate or consume electrons, influencing the electrochemical potential at the alloy surface.